2022
DOI: 10.3389/fsurg.2022.862348
|View full text |Cite
|
Sign up to set email alerts
|

Role of three dimensional (3D) printing in endourology: An update from EAU young academic urologists (YAU) urolithiasis and endourology working group

Abstract: The management of nephrolithiasis has been complemented well by modern technological advancements like virtual reality, three-dimensional (3D) printing etc. In this review, we discuss the applications of 3D printing in treating stone disease using percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS). PCNL surgeries, when preceded by a training phase using a 3D printed model, aid surgeons to choose the proper course of action, which results in better procedural outcomes. The 3D printed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Accurate anatomic models can be constructed using 3D printers, aiding in a more realistic and detailed representation of the urinary tract geometry compared to 2D pictures accessed through CT and MRI scans. 35 The main directions in which 3D models can assist urolithiasis management are training, pre-procedural planning, and patient counselling. 36 In a study by Xu et al, 3D models from patients with staghorn stones were created and utilized for training and preoperative planning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate anatomic models can be constructed using 3D printers, aiding in a more realistic and detailed representation of the urinary tract geometry compared to 2D pictures accessed through CT and MRI scans. 35 The main directions in which 3D models can assist urolithiasis management are training, pre-procedural planning, and patient counselling. 36 In a study by Xu et al, 3D models from patients with staghorn stones were created and utilized for training and preoperative planning.…”
Section: Resultsmentioning
confidence: 99%
“… 38 After training completion, residents of the two groups were asked using a specific questionnaire about their training experience and authors concluded that 3D printed PCNL models led to significantly improved response metrics compared to simulator for all indices, namely X-ray guided puncture, guidewire placement, identification of proper calyx, placement of nephrostomy tube, assessment of kidney anatomy, feedback of tissue model and discussion about errors. 35 , 38 Going a step further, Golab et al utilized 3D printed guides created using CT images, to perform renal puncture in a patient with horseshoe kidney and reported that the needle successfully reached the stone in the patient's kidney. 39 Cost implications should also be highlighted, since VR trainers seem to come at costs of ~100.000 dollars, which is clearly not viable for most teaching centers around the globe.…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing trend of the use of simulators and simulation training over the last decade, and it is difficult to ignore the leading role simulators are playing in surgical improvement[ 10 ]. Our research found numerous papers on the application of simulation devices, especially phantoms and 3D printed models, for testing new technological devices.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been performed on application of simulators in training of residents and expert surgeons, with focus on costs, performance, learning curve and standardized protocols[ 9 ]. As gathered from data, simulators are increasingly relied on for urology resident training worldwide[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…CT urogram is often the study of choice. However, innovative meticulous planning uses artificial intelligence (AI) and 3D [26].…”
Section: Urolithiasis In Anomalous Kidneysmentioning
confidence: 99%